Pro-Environmental Behavior of Coastal Communities: A Review of the Role of Eco-Anxiety and Psychological Well-Being - Kahar, Amalia S.J; Kasim, Indah Luthfiyah (Psikostudia : Jurnal Psikologi, 2026)
Coastal communities are vulnerable to the impacts of environmental change, thus requiring pro-environmental behavior that is not only influenced by knowledge and environmental conditions but also psychological factors. This study aims to determine the role of eco-anxiety and psychological well-being (PWB) on pro-environmental behavior in coastal communities in North Maluku. The method used is a quantitative approach with a correlational design, involving 117 respondents as the research sample. The questionnaire used in this study consists of three scales, namely, Larson's Pro-environmental Behavior (PEiB) scale, Hoog's Eco-Anxiety Scale (HEiAS), and Ryff's Psychological Well-Being scale. Data analysis uses multiple regression analysis. The research results show that there is a highly significant positive relationship between eico anxiety and psychological well-being (PWB) with pro-environmental behavior with a significance level of 0.008 (p < 0.01). The results of the minor hypothesis test eico anxiety with pro-environmental behavior are very significant (p = 0.006). The results of the study are expected to provide a more comprehensive understanding of the psychological factors that encourage pro-environmental behavior in coastal communities and can be a reference for designing psychological-based interventions and community-based policies in coastal environmental conservation efforts.